Pemberdayaan Ibu – Ibu Rumah Tangga dalam Kewirausahaan Keluarga Melalui Usaha Rumahan - Agus Susanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PKM) aims to strengthen the role of housewives who are members of Dasa Wisma groups in family entrepreneurship through the development of home-based businesses The program partners were the Teratai 2 Dasa Wisma women group located in Taman Puri Sartika Housing Complex, RT 05 RW 12, Semarang City, consisting of 17 participants. The main problems faced by the partners included limited entrepreneurial knowledge, low utilization of home-based business potential, and suboptimal management of family businesses. The implementation methods included counseling, training, discussions, and simple mentoring related to family entrepreneurship concepts, identification of business opportunities, and management of home-based businesses. The results of the program showed an improvement in participants’ understanding of family entrepreneurship, increased entrepreneurial motivation, and the emergence of various home-based business ideas with the potential to be independently developed. This community service program is expected to serve as an initial step in encouraging family economic independence through the active role of housewives.